The 1983 Strike-Hard Campaign in China: a Moral Panic? - Dai, Mengliang (The British journal of criminology, 2020)
Though more than three decades have passed since the launch of Strike Hard in 1983, its impact on crimes remains. Most of the literature on the campaign so far has been theoretically and methodologically limited. Using historical materials and interview data, this paper establishes an integrated theoretical framework and aims at investigating whether and how a moral panic was constructed. This study argues that the top leader played a decisive role in engineering the moral panic during the 1983 Strike Hard operated through a top-down approach under the Chinese political structure. In short, exploring events from the perspective of moral panic, this study gives a deep insight into the Chinese criminal justice system in response to crimes.